2018
DOI: 10.1126/sciadv.aat0496
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, noninvasive detection of Zika virus in Aedes aegypti mosquitoes by near-infrared spectroscopy

Abstract: We report the first use of near-infrared spectroscopy for rapid, low-cost, noninvasive detection of Zika virus in Aedes aegypti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 40 publications
1
91
0
Order By: Relevance
“…The far-(30-400 cm -1 ), mid-(400-4,000 cm -1 ), and nearinfrared (4,000-10,000) regions of the mosquito spectra were compared ( Supplementary Figure 4). The far-and nearinfrared regions were essentially featureless in dried mosquitoes, unlike the spectra observed in the literature 37,39,40,50,51 that show the intense signals of liquid water as they were measured in undried mosquitoes (Supplementary Figure 5). However, the mid-infrared region showed a large number of well-defined intense peaks, which are easily identifiable as coming from the chemical components of the cuticle (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The far-(30-400 cm -1 ), mid-(400-4,000 cm -1 ), and nearinfrared (4,000-10,000) regions of the mosquito spectra were compared ( Supplementary Figure 4). The far-and nearinfrared regions were essentially featureless in dried mosquitoes, unlike the spectra observed in the literature 37,39,40,50,51 that show the intense signals of liquid water as they were measured in undried mosquitoes (Supplementary Figure 5). However, the mid-infrared region showed a large number of well-defined intense peaks, which are easily identifiable as coming from the chemical components of the cuticle (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 54%
“…Indeed, microorganism infections alter mosquito physiology and could directly or indirectly modify its cuticular composition. For example, in the dengue and Zika vector Ae-des aegypti mosquitoes, infrared spectroscopy has recently been developed to detect Zika virus, 39 and the bacterial endosymbiont Wolbachia. 43,50 The accuracy and generalisability of the MIRS approach presented here to determine key mosquito traits shows that this tool can be used to assist the evaluation of vector control intervention in large mosquito populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another study reported that near-infrared spectroscopy (NIRS) is a rapid, reagent-free, and cost-effective tool used to detect ZIKV noninvasively in heads and thoraces of intact Aedes aegypti mosquitoes with high prediction accuracies relative to quantitative RT-qPCR reaction. Perhaps this technique could be extended upon for identifying probable arbovirus hotspots to guide spatial prioritization of vector control (Fernandes et al 2018). Recently developed surface plasma resonance (SPR) spectroscopy was developed to be a valuable optical biosensor and potential method for diagnosis of dengue virus E-protein and also for identification of antibodies to DENV antigen.…”
Section: Spectroscopy-based Immunodetectionmentioning
confidence: 99%
“…Many of these assays are laborious and laboratory-based and require expensive and bulky instruments, making them incompatible with low-resource regions (24). Recently, several novel, advanced point-of-care (POC) diagnostic measures have been developed for detecting mosquito-borne viruses in the field, including honey-baited nucleic acid preservation cards (25, 26), loop-mediated isothermal amplification (LAMP) (27), biosensors (28), and adaptations of near-infrared spectrometry techniques (29). However, these techniques have documented limitations, including cross-reactivity with other flaviviruses or requirements for training on specialized equipment, making the adoption of these new diagnostic tools difficult (30, 31).…”
Section: Introductionmentioning
confidence: 99%